Obstructed hemivagina with uterus didelphys and ipsilateral renal anomaly syndrome: a rare presentation with pyocolpos - Saber, Nicolas; Barakat, Fatima; Awala, May; Nakhel, Rayan; Saber, Melhem; Barakat, Hassan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Uterus didelphys with obstructed hemivagina and ipsilateral renal agenesis (OHVIRA syndrome) is a rare congenital anomaly of the female genital tract. It typically presents after menarche with progressive pelvic pain due to hematocolpos formation, leading to dysmenorrhea and a pelvic mass. We report the first documented Lebanese case of OHVIRA syndrome, involving an 18-year-old woman who presented with recurrent pelvic pain particularly during menstruation irregular cycles, and yellowish vaginal discharge. Pelvic ultrasonography, computed tomography, and magnetic resonance imaging confirmed the diagnosis. The distinct rarity of this case lies in the presence of pyocolpos, an uncommoun complication. The patient underwent surgical excision of the obstructing vaginal septum, with drainage of approximately 100 ml of purulent fluid. A Penrose drain was placed within the obstructed hemivagina the first reported use of this technique in Lebanon to ensure continuous drainage and prevent postoperative re-obstruction. The patient experienced complete symptom relief following the procedure.